Investigating the anti-inflammatory effects of plant derived compounds in tuberculosis using the THP-1 macrophage model - Rajh, Caryn (Department of Clinical Laboratory Sciences, 2024)
Background Tuberculosis (TB) is a highly communicable disease that is caused by the bacillus, Mycobacterium tuberculosis. TB is responsible for devastating morbidity and mortality worldwide, especially in the developing world. TB can be effectively treated with the currently available drugs; however, poor adherence to therapy and the emergence of drug resistant bacteria has significantly impaired efforts to eradicate TB. Therefore, new therapies and therapeutic strategies are required to combat TB. One of the proposed new strategies is to develop host-directed therapies (HDTs) that are aimed at boosting the host's innate ability to fight the infection and ameliorate the deleterious tissue pathology associated with advanced TB. Repurposed drugs and plant-derived compounds with antiinflammatory effects have been explored for potential use as HDT's. Objectives To evaluate the anti-inflammatory effects of plant-derived compounds in macrophages infected with live Mtb strain H37Rv. Results We found that Ruscogenin failed to modulate cytokine secretion in macrophages that were either infected with live Mtb strain H37Rv or macrophages that were pre-treated with the compound prior to infection with Mtb, except for lowering IL-6 secretion. Leonurine significantly lowered the levels of IL-1β, TNF and IL-6 in macrophages that were pre-treated with the compound for 24 hours prior to infection with live Mtb. We also showed that Withaferin A decreased IL-1β and IL-6 secretion in macrophages infected with Mtb prior to treatment with the compound. Finally, pre-treating macrophages with Withaferin A prior to infection with Mtb decreased the secretion of TNF and IL-6 compared to the untreated and infected macrophages. Conclusion Leonurine and Withaferin A appear to possess anti-inflammatory effects in macrophages infected with live Mtb. Their potential use as HDTs needs to be explored further in animal models.